2005
DOI: 10.1089/jam.2005.18.354
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Pediatric Aerosol Delivery: Importance of Facemask

Abstract: We have quantified in vitro the influence of the facemask on the amount of drug delivered (e.g., inhaled mass) by jet nebulizer and pressurized metered dose inhaler (pMDI) valved holding chamber (VHC) combinations (non-detergent-coated and detergent-coated). Pediatric breathing patterns were used with a breathing simulator, which was connected to a face onto which each device was positioned. An inhaled mass filter interposed between the simulator and the face captured the aerosolized drug. Budesonide inhalatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 16 publications
0
47
0
Order By: Relevance
“…[35][36][37][38] One study 39 showed the opposite effect in a pediatric lung model, wherein a standard bottom-loaded aerosol mask resulted in greater drug delivery than a frontloaded design. It is important to note that a common nebulizer was not used with each of the different face masks during the testing, so it is unclear if these results were based solely on the mask or the nebulizer being used.…”
Section: Interface Selectionmentioning
confidence: 99%
“…[35][36][37][38] One study 39 showed the opposite effect in a pediatric lung model, wherein a standard bottom-loaded aerosol mask resulted in greater drug delivery than a frontloaded design. It is important to note that a common nebulizer was not used with each of the different face masks during the testing, so it is unclear if these results were based solely on the mask or the nebulizer being used.…”
Section: Interface Selectionmentioning
confidence: 99%
“…Even small leaks of 0.5 cm around the face mask decrease drug inhaled by children and infants by more than 50%. [30][31][32][33][34] Delivery of aerosolized medications in a blow-by fashion is commonly used for crying babies or uncooperative children, where the nebulization port of a nebulizer is directed toward the patient's face. Studies have documented blow-by medication administration is less efficient, compared with a face mask, as aerosol drug deposition decreases significantly with distance, and this use should be discouraged.…”
Section: Other Nuances and Characteristics Of Svnsmentioning
confidence: 99%
“…Studies have documented blow-by medication administration is less efficient, compared with a face mask, as aerosol drug deposition decreases significantly with distance, and this use should be discouraged. 30,[34][35][36] In summary, while the domain of SVNs can be highly variable, based on the nuances and characteristics described previously, the entire category has some common advantages and disadvantages, which are listed in Table 6.…”
Section: Other Nuances and Characteristics Of Svnsmentioning
confidence: 99%
“…The use of a facemask requires a tight seal between the face and the mask to reduce drug waste, avoid deposition in the eyes, and to ensure delivery of an appropriate dose to the airways [53]. Another common issue in aerosol delivery is crying, which occurs in 38% of children, M A N U S C R I P T…”
Section: Nebulization In Young Children: Special Considerationsmentioning
confidence: 99%